Off-Season Effects on Functional Performance, Body Composition, and Blood Parameters in Top-Level Professional Soccer Players. Issue 4 (April 2017) - Requena, Bernardo; García, Inmaculada; Suárez-Arrones, Luis; Sáez de Villarreal, Eduardo; Naranjo Orellana, José; Santalla, Alfredo
Abstract : Abstract: Requena, B, García, I, Suárez-Arrones, L, Sáez de Villarreal, E, Naranjo Orellana, J, and Santalla, A. Off-season effects on functional performance, body composition, and blood parameters in top-level professional soccer players. J Strength Cond Res 31(4): 939–946, 2017—To examine the effects of a standard off-season period (OSP) on aerobic, sprint, and jumping performances, and body and blood composition in a top-level soccer team. Nineteen soccer players were measured. The OSP included to 2 weeks of no training (resting phase) and a 4-week period of moderate-training load (phase in which each player performed the vacation exercise plan). Player's functional performance (15- and 30-m sprint times [seconds], vertical jump [meter], and incremental field test Vam-Eval [kilometer per hour]), percentage of body fat (%) and blood composition (hematological and biochemical data) were measured at mid-season, end-season, and after the OSP. The percentage of body fat was nonaltered during the competitive season (10.8 ± 3.6 and 10.5 ± 3.5%) and increased significantly after the OSP (11.6 ± 3.6%, p ⩽ 0.05). Similarly, the maximal aerobic speed ( V Vam-Eval ) velocity (kilometer per hour) decreased ( p ⩽ 0.05) from 17.4 ± 1 and 17.3 ± 1.2 during the competitive season to 16.6 ± 0.9 after the OSP. The hematocrit and blood hemoglobin concentration increased ( p ⩽ 0.05) during the OSP, showing a blood hemoconcentration adaptation. However, sprint time (seconds) and jump height (meters) showed no significant changes after the OSP. Soccer players maintained their functional performance during high-intensity activities such as jumping or sprinting after the OSP proposed. By contrast, there was a decrease in aerobic performance ( V Vam-Eval ) accompanied by a blood hemoconcentration, and an increase of body fat mass associated with a reduction of fat-free mass of the lower limbs. Our data suggest that an end-season evaluation is needed to design holiday training programs focused on regaining aerobic capacity and body composition.